São Bernardo: construção do romance pela memória - Furtado, Pedro Barbosa Rudge [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This paper concentrates on demonstrating that the novel called São Bernardo ,written by Graciliano Ramos, utilizes some literary strategies that cause the effect of being built by rememorizations, which is a vital aspect of several of the author’s titles. Such objective is reached via the analyses of how the following narrative categories: focalization, narrator, characters, story and time converge toward the elaboration of the memory and the comparison between this construction on São Bernardo and Angústia. In order to be successful on this task, three groups of study constitute our theoretical basis: a) critical essays concerning Graciliano Ramos; b) theoretical propositions about the narrative categories; c) academic articles on the constitution of memory. Papers composed by Antonio Candido, Alfredo Bosi, Sonia Brayner, Luís Costa Lima and others are part of the first group. The second one is constituted by propositions of Gérard Genette, Benedito Nunes etc. Finally, on the last one, we find Paul Ricouer and Henri Bergson

O presente trabalho concentra-se na demonstração de que o romance São Bernardo de Graciliano Ramos utiliza determinados recursos literários que trazem o efeito de ser construído através de rememorações; aspecto que é fundamental em algumas obras do autor. Tal objetivo é atingido por meio da análise da maneira como as categorias narrativas, como focalização, narração, personagem, história e tempo convergem para a elaboração da memória e, ainda, da comparação dessa construção entre São Bernardo e Angústia. Para tanto, as balizas teóricas são constituídas em três grupos de estudos: a) ensaios críticos sobre Graciliano Ramos; b) proposições teóricas sobre as categorias da narrativa; c) ensaios sobre a constituição da memória. Fazem parte do primeiro grupo ensaios como os de Antonio Candido, Alfredo Bosi, Sonia Brayner, Luís Costa Lima, entre outros. Do segundo grupo, contamos com propostas de Gérard Genette, Benedito Nunes e outros. No terceiro grupo temos Paul Ricouer e Henri Bergson
Keywords: Ramos, Graciliano 1892-1953; Literatura; Literatura brasileira; Brazilian literature